Pengaruh Moderasi Beragama terhadap Kehidupan Sosial Masyarakat Desa Timbang Lawan - Samsudin Samsudin; Rama Sandy Permana; Asma Alya Najiha; Ayu Febrianti Adha; Aulia Fitriani Munthe (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Religious moderation is an essential aspect of building a tolerant and harmonious society, particularly in rural areas. This study aims to analyze the implementation of religious moderation through the KKN program in Desa Timbang Lawan and assess its impact on the social life of the community. This research employs a qualitative method, using a descriptive approach to comprehensively depict program implementation. Data were collected through participant observation, interviews with residents and KKN participants, and documentation of activities. The KKN activities included the festival of righteous children, anti-bullying education, dissemination of the concept of religious moderation in schools, communal work at the mosque and village environment, Independence Day competitions, Yasin recitation, and teaching children to recite the Quran. The results show that these activities successfully enhanced tolerance, solidarity, and social participation among residents, while fostering collective awareness of the importance of religious moderation. Additionally, direct interaction between KKN students and the community provided a constructive discussion space and improved practical understanding of moderation values. These findings contribute significantly to the development of literature on the implementation of religious moderation in rural social contexts and serve as a reference for future KKN programs. Practically, this study emphasizes that a participatory approach and activities involving all community layers are key to the successful implementation of religious moderation.